The Semantics of the Oath in the Holy Qur’an, Surat al-Tin - al-Ansi, Abdel Salam Hammoud Ghaleb (Dzil Majaz: Journal of Arabic Literature, 2023)
The section in the Holy Quran of the Arabic methods used largely in the Holy Quran and has specific structures and tools, and also has a clear significance and connotations indicating the importance of the divider and its status as well as attract the attention of the listener to what will be mentioned of the words follow the oath, and this method was used by the Arabs and significantly had an impact in the ears of the hearers in the days of the Prophet peace be upon him as well as the section comes to confirm the saying and install him, it is worth us to search and enrich the subject  With regard to the semantics of the section in the Holy Qur'an in general and in particular in Surat Al-Tin, and its section with four things mentioned in the surah . There is no doubt and no doubt that the divided by it in Surat Al-Tin has clear connotations and great importance Ford oath by God Almighty, and some understood those connotations and ignorance of some, and some did not imagine the status and importance of figs and olives as a scientific aspect after the development of science and global openness today, scientists discovered today new properties and features in figs and olives as well as the medical benefits of them and this is one of the implications of the section of the thing for its status and importance has been known by some and absent from some has used the researcher The inductive approach as well as descriptive and analytical to discuss the semantics of the section models applied in the form of figs, and the research leads us to the existence of importance and clear indications of what has been sworn in Surat figs, whether the medical benefit of figs and olives, as well as the aspect of security and safety and its importance to human life, what God swore by in his book was not in vain or neglected, and modern science is still discovering scientific implications of what God swore by in his book in various cosmic fields and others.